STRATEGI KOMUNIKASI PERSUASIF GUS MUHAMMAD IQDAM DALAM MEMBANGUN BUDAYA ISLAM DI MAJELIS TAKLIM SABILU_TAUBAH BLITAR - Arridho, Muhamad Taufiq; Islam, Ahmad Fakhruddin Fajrul; Muhamad Taufiq Arridho; Ahmad Fakhruddin Fajrul Islam (Masjiduna : Junal Ilmiah Stidki Ar-Rahmah, 2024)
This research discusses how Gus Muhammad Iqdam uses persuasive communication strategies to build Islamic culture at Majelis Taklim Sabilu_Taubah Blitar. The main purpose of this study is to understand the process of persuasive communication strategies used by Gus Muhammad Iqdam in shaping Islamic culture at Majlis Taklim. A qualitative approach was used to describe field data with a focus on Gus Muhammad Iqdam's persuasive communication strategy in shaping Islamic culture at Majlis Taklim. Data collection methods involved observation, interviews, and documentation. The data analysis process involved data reduction, data presentation, and conclusion drawing. Data validity was strengthened through credibility techniques, such as careful observation and triangulation. The results showed that the implementation of persuasive communication strategies by Gus Muhammad Iqdam in building Islamic culture in the Taklim Assembly was effective. In conclusion, the persuasive communication approach applied by Gus Muhammad Iqdam succeeded in strengthening Islamic culture in Majelis Taklim. This strategy is effective in shaping and strengthening religious and cultural values in the taklim assembly, confirming the important role of persuasive communication in building religious and cultural values in the environment concerned.